Features Of Surgical Management in Acute Cholecystitis in Patients of Elderly and Old Age Complicated by Bile Ducts - Kurbaniyazov Zafar Babazhanovich; Rakhmanov Kosim Erdanovich; Nazarov Zokir Norzhigitovich; Abdurakhmanov Diyor Shukurillaevich (Periodica Journal, 2022)
Optimal schemes of surgical treatment of acute cholecystitis complicated by obstruction of the bile ducts have been developed using various methods of X-ray endoscopic decompression and sanitation of the biliary tract (cholecystostomy, papillotomy). A differentiated approach to determining the scope of the operation, depending on the degree of operational and anesthetic risk, is proposed. The expediency of expanding the indications for cholecystectomy from a mini-access in combination with transcholedochal papillotomy, which adequately restores the outflow of bile into the duodenum, while limiting the indications for open laparotomy, has been shown. The significance of endoscopic obliteration of the gallbladder in the complex treatment of patients after cholecystostomy with an unreduced risk of radical surgery due to concomitant diseases was determined.
Keywords: cholecystostomy; papillotomy; choledocholithiasis; fibrocholedochoscopy